Myo‐inositol trispyrophosphate‐mediated hypoxia reversion controls pancreatic cancer in rodents and enhances gemcitabine efficacy. Issue 11 (25th November 2013) - Raykov, Zahary; Grekova, Svitlana P.; Bour, Gaétan; Lehn, Jean Marie; Giese, N.A.; Nicolau, Claude; Aprahamian, Marc
<x xml:space="preserve">Abstract</x> Hypoxia and dysfunctional tumor vessels represent a prominent feature of pancreatic cancer, being, at least in part, responsible for chemotherapy resistance and immune suppression in these tumors. We tested whether the increase of oxygen delivery induced in vivo by myo‐inositol trispyrophosphate (ITPP) can reverse hypoxia, control tumor growth and improve chemotherapy response. Tumor size, metastatic development (microcomputed tomography scan follow‐up) and the survival of rats and nude or NOD.SCID mice, (bearing syngenic rat and MiaPaCa2‐ or patient‐derived pancreatic tumors), were determined on ITPP and/or gemcitabine treatment. Partial oxygen pressure, expression of angiogenic factors and tumor histology were evaluated. Infiltration and oxidative status of immune cells, as well as chemotherapy penetration in tumors, were determined by fluorescence‐activated cell sorting, fluorometry, nitric oxide release assays, Western blot and confocal microscopy. Weekly intravenous ITPP application resulted in the inhibition of metastasis development and restricted primary tumor growth, showing a superior effect on the rats' survival compared with gemcitabine. ITPP treatment restored tumor normoxia and caused a reduction in hypoxia inducible factor‐1α levels, with subsequent VEGF and Lox downregulation, resulting in improved vessel structure and decreased desmoplasia. The latter effects translated into elevated immune cells influx and improved susceptibility to gemcitabine treatment. Growth of human pancreatic tumor xenografts was strongly inhibited by administration of ITPP. ITPP exploits a two‐stage mechanism causing rapid, early and sustainable late stage normoxia. This is due to the angiogenic factor modulation and vascular normalization, leading to enhanced chemotherapy delivery and synergistic life prolongation, on combination with low doses of gemcitabine.